Simula Research Laboratory by Thinking Constantly about it - Tveito, Aslak; Bruaset, Are Magnus; Lysne, Olav.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The Simula Research Laboratory, located just outside Oslo in Norway, is rightly famed as a highly successful research facility, despite being, at only eight years old, a very young institution. This fascinating book tells the history of Simula, detailing the culture and values that have been the guiding principles of the laboratory throughout its existence. Dedicated to tackling scientific challenges of genuine social importance, the laboratory undertakes important research with long-term implications in networks, computing and software engineering, which includes offering a Centre of Excellence in biomedical computing. The text covers every angle: the laboratory's background and political context, the work it has completed, its approach to the education and development of its researchers, and the organisation's efforts to promote the application of its research results. The key research projects and results are covered in separate chapters, each of which is preceded by a thumbnail description of the project and how the research is useful for society. As well as explanatory text, the other chapters feature interviews with major players in the facility's history, both inside Simula, among its collaborators, and in Norwegian society at large.
The Scene -- What Would you do if you Suddenly got an Annual Grant of About Ten Million Dollars? -- By Thinking Constantly About It -- The Simula Culture - How we do Research, Education and Innovation -- Impressed with Targeted Research Strategy -- The Hamming Experience -- Richard Hamming - You and Your Research -- Simula Research Laboratory $1 (BA Different Research Institution -- IT Fornebu and the Political Battle that led to the Creation of Simula -- The Right Step at the Right Time -- A Brief History of Norwegian Science and Research Policy -- Simula $1 (BThe Language -- Basic Research -- to Basic Research -- Networks and Distributed Systems $1 (BWhy, What, How and What$1 (Bs Next -- Scalable Interconnection Networks -- Providing Resilience in Communications Networks -- From Gilgamesh to Star Wars -- RELAY $1 (BOn the Performance and Resource Utilisation of Time-Dependent Large-Scale Distributed Systems -- Scientific Computing - Why, What, How and What's Next -- Catching the Beat -- Computer Simulations of the Heart -- A Message from the Heart -- Can ECG Recordings and Mathematics tell the Condition of Your Heart? -- Past and Future Perspectives on Scientific Software -- Software Engineering $1 (BWhy, What, How and What$1 (Bs Next -- A Matter of Judgement -- Software Development Effort Estimation $1 (BDemystifying and Improving Expert Estimation -- Faulty Until Proved Correct -- Software Verification $1 (BA Scalable, Model-Driven, Empirically Grounded Approach -- The industry is our lab $1 (BOrganisation and Conduct of Empirical Studies in Software Engineering at Simula -- A Series of Controlled Experiments on Software Maintenance -- Research Education -- Educating Researchers $1 (Ba Virtue of Necessity -- Thinking Outside the Box -- A Little Competition and a Lot of Cooperation -- Are you Planning to Take a PhD? -- An Extraordinary Investment -- Simula can do Much Better! -- Achieving Relevance -- Research Applications -- Bridging the Gap Between Industry and Research -- Making the Invisible Visible -- Turning Rocks into Knowledge -- A Tale of Three Start-ups -- Spinning Off from Simula -- We're Not a Telco, We're a Webco.s
Keywords: Mathematics; Computer network architectures; Software engineering; Physiology -- Mathematics; Computer science -- Mathematics; Mathematics; Computational Mathematics and Numerical Analysis; Applications of Mathematics; Computer Systems Organization and Communication Networks; Physiological, Cellular and Medical Topics; Software Engineering/Programming and Operating Systems